南大洋N_2O研究进展及测量新技术展望 - 张介霞; 詹力扬; 陈立奇 (2013)
氧化亚氮(n2O)是大气最重要的温室气体之一,能在大气滞留120年,其增温潜势是CO2的310倍。工业革命以来,大气中n2O浓度已增加了20%,但海洋仍然是大气n2O重要的自然源,占总自然源的1/3左右。南大洋是全球海洋系统重要组成部分,具有独特的水文特征。模式研究表明其是大气n2O的重要源。然而,受制于恶劣的海况条件,南大洋航次观测数据至今十分稀少。简单综述了南大洋n2O研究的重要性、研究进展及现场观测技术和模型应用的结果及其存在的问题。强调稳定同位素方法的运用将为海洋n2O形成机制研究提供新的强有力手段,另外,研发高精度的走航观测技术也是今后n2O研究取得突破的必须努力方向。展望激光光谱技术的运用对南大洋n2O研究的突破以及海冰中n2O浓度测量技术的发展,将对评估海冰在形成和融化过程中可能存在的源汇提供直测证据。 Nitrous oxide is an important greenhouse gas,which has a long lifetime of about 120 years and has a 310 times greenhouse effect than CO2.Since the industrial revolution,the atmospheric N2O concentration has increased significantly by 20%.Ocean is a net source,about 1 /3 of total oceanic souce.Southern Ocean is an important part of the global ocean system,has a unique hydrological characteristics.So far it is regarded as a significant natural source to the global N2O flux according to the model studies.However,the field work is very limit,due to the fierce in situ conditions.The importance of N2O reseaches of Southern Ocean,progresses of nitrous oxide researches,especially new technologies applied to underway N2O measurements in the Southern Ocean are reviewed.The advance of field,model studies and their problems or uncertainties that need to be resolved are also discussed.The using of stable isotope methods will provide powerful tools for marine N2O mechanism.Development of highprecision monitoring technology is generally the driving force of future research.Developing techniques of laser spectroscopy in marine N2O studies and measurment of N2O in sea ice will provide powerful tools to differeciate the N2O source sink characteristic,constrain their budget and formation mechanism in region such as Southern Ocean. 中国极地科学战略青年基金项目“普里兹湾N2O分布特征及可能形成机制”(编号:20120310)资助